Teknologi bayi tri-induk menurut bioetika Islam berasaskan Maqasid al-Shariah / Abdul Halim Ibrahim - Abdul Halim, Ibrahim (2017)
Tri-parent baby technology is a medical treatment in the form of assisted reproductive technology (ART) with the purposes of reducing or eliminating the risk of maternal inheritance of mitochondrial DNA (mtDNA) disorders. The development of this technology has implications on the Muslims’ way of life, in the context of the five essential components of al-ḍarūriyyāt al-khams namely the protection of faith, life, lineage, intellect, and wealth. The objectives of this research are to explain what mitochondrial DNA (mtDNA) disorders are, and the role of ART in overcoming the disorders through the application of tri-parent baby technology, as well as the Islamic view on genetically related diseases; to explain concept of Islamic bioethics based on maqāṣid al-Sharīʿah; to analyse Islamic views and decrees on ART-related diseases and implications of the tri-parent baby technology on stakeholders; and to assess status of the tri-parent baby technology from the perspective of Islamic bioethics based on maqāṣid al-Sharīʿah. This research uses the critical interpretation approach as this is an ethical, interpretive, textual, and contextual research. This study analyses the tri-parent baby technology from three major aspects namely intention/cause, methods, and final goal/output of the technology by looking at their positive and negative implications towards al-ḍarūriyyāt al-khams. Subsequently, the status of these implications of the three aspects towards al-ḍarūriyyāt al-khams is determined based on maqṣad standardised determination methods from the view of preservation of human interests (ḍarūriyyāh, ḥājiyyah, or taḥsīniyyah), inclusivity of stakeholders (ʿāmmah or khāṣṣah), and status of certainty (qaṭʿiyyah, ẓanniyyah or wahmiyyah). This study of the tri-parent baby technology from the perspective of Islamic bioethics based on maqāṣid al-Sharīʿah shows that there are elements of maternal lineage confusion in the tri-parent baby due to vii both pronuclear transfer (PNT) and maternal spindle transfer (MST) techniques involving the use of third party gamete cells, thus violating the preservation of lineage. Mixing of maternal lineage of the tri-parent baby will threaten the Islamic family institution because the technology leads to confusion that shakes the Islamic concept of motherhood and family. Confusion of maternal lineage gives significant implications involving marriage, social relationship, and property heritance, hence indirectly threatenning the preservation of religion. Also, this study shows that the safety of the tri-parent baby technology application on human is yet assured. The argument that this technology will preserve the lineage by conceiving healthy baby is inapplicable because conception via this technology is only an act of embellishment (taḥsīniyyah) to fulfill the mtDNA affected couple to have a genetically related child. There are other options for this couple to have a child such as through preimplantation genetic diagnosis PGD. Therefore, this study suggests that the tri-parent baby technology should not be permitted for Muslims in Malaysia. The impermissibility of tri-parent baby technology is also a preemptive measure (sadd al-dharīʿah) because there are elements of mixed lineage in the techniques of the technology. This is to avoid the conceived baby from being an illegitimate child.